Midkine - a novel player in cardiovascular diseases - Majaj, Marina; Weckbach, Ludwig T. (Frontiers in Cardiovascular Medicine, 2022)
Midkine (MK) is a 13-kDa heparin-binding cytokine and growth factor with anti-apoptotic, pro-angiogenic, pro-inflammatory and anti-infective functions, that enable it to partake in a series of physiological and pathophysiological processes. In the past, research revolving around MK has concentrated on its roles in reproduction and development, tissue protection and repair as well as inflammatory and malignant processes. In the recent few years, MK's implication in a wide scope of cardiovascular diseases has been rigorously investigated. Nonetheless, there is still no broadly accepted consensus on whether MK exerts generally detrimental or favorable effects in cardiovascular diseases. The truth probably resides somewhere in-between and depends on the underlying physiological or pathophysiological condition. It is therefore crucial to thoroughly examine and appraise MK's participation in cardiovascular diseases. In this review, we introduce the MK gene and protein, its multiple receptors and signaling pathways along with its expression in the vascular system and its most substantial functions in cardiovascular biology. Further, we recapitulate the current evidence of MK's expression in cardiovascular diseases, addressing the various sources and modes of MK expression. Moreover, we summarize the most significant implications of MK in cardiovascular diseases with particular emphasis on MK's advantageous and injurious functions, highlighting its ample diagnostic and therapeutic potential. Also, we focus on conflicting roles of MK in a number of cardiovascular diseases and try to provide some clarity and guidance to MK's multifaceted roles. In summary, we aim to pave the way for MK-based diagnostics and therapies that could present promising tools in the diagnosis and treatment of cardiovascular diseases.
Gesehen am 10.01.2023